2003
DOI: 10.1016/s0042-6822(02)00100-9
|View full text |Cite
|
Sign up to set email alerts
|

Infection with the oncogenic human papillomavirus type 59 alters protein components of the cornified cell envelope

Abstract: Infection of the genital tract with human papillomaviruses (HPVs) leads to proliferative and dysplastic epithelial lesions. The mechanisms used by the virus to escape the infected keratinocyte are not well understood. Infection of keratinocytes with HPV does not cause lysis, the mechanism used by many viruses to release newly formed virions. For HPV 11, a type associated with a low risk of neoplastic disease, the cornified cell envelope (CCE) of infected keratinocytes is thin and fragile, and transcription of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Anogenital HPV infection produces late terminal differentiation changes and changes to the cornified envelope of mucosal epithelium (20, 21). We show that cutaneous HPV8 early genes down-regulate filaggrin, a key late terminal differentiation marker that is processed through multiple steps to produce a small molecular weight form crucial for terminal differentiation [Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anogenital HPV infection produces late terminal differentiation changes and changes to the cornified envelope of mucosal epithelium (20, 21). We show that cutaneous HPV8 early genes down-regulate filaggrin, a key late terminal differentiation marker that is processed through multiple steps to produce a small molecular weight form crucial for terminal differentiation [Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We speculate that AKT1 activity is targeted by cutaneous HPVs to render the cornified envelope “fragile” to effect escape. Anogenital HPV-associated change to cornified envelopes is well documented and also achieved through changes to late terminal differentiation proteins (20, 21) and, possibly, by expression of the HPV E1∧E4 early gene, which binds keratin and causes keratin collapse (27). However, cutaneous papillomaviruses express an E1∧E4 protein that is unable to induce intermediate filament collapse (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S100A8 and S100A9 , however, do not appear to be the only members of EDC regulated by HPV. Involucrin ( IVL ) and loricrin ( LOR ) are transcriptionally downregulated by E6 and E7 HPV oncoproteins in proliferating and differentiating human foreskin keratinocytes (Lehr and Brown 2003; Gyöngyösi et al 2012). Specifically, involucrin is indirectly suppressed by E6 oncoprotein through HPV-mediated downregulation of transcription factor C/EBPα (Marthaler et al 2017).…”
Section: Role Of Calprotectin In Head and Neck Carcinogenesismentioning
confidence: 99%
“…Indeed, HPV 16 E6 was shown to modulate the expression of several differentiation-associated genes in human foreskin keratinocytes [13]. Using a xenograft model, Lehr and co-workers showed that infection of human keratinocytes by certain HPVs (type 11 and 59) causes altered expression of certain CCE (cornified cell envelope) proteins, such as loricrin and small proline rich proteins (SPRR), both on the mRNA and on the protein level [14,15]. However, it is not known whether the HPV oncoproteins have effects on the promoters of differentiation-regulated genes or exert their effects post-transcriptionally.…”
Section: Introductionmentioning
confidence: 99%